Cordycepin Inhibits Drug-resistance Non-small Cell Lung Cancer Progression by Activating AMPK Signaling Pathway. (June 2019) - Wei, Chunli; Yao, Xiaojun; Jiang, Zebo; Wang, Yuwei; Zhang, Dianzheng; Chen, Xi; Fan, Xingxing; Xie, Chun; Cheng, Jingliang; Fu, Junjiang; Leung, Elaine Lai-Han
Graphical abstract: Abstract: Lung cancer is the most commonly diagnosed cancer worldwide and it is also the most leading cause of cancer-related deaths. Although multiple generations of targeted therapeutic drugs such as gefitinib and afatinib specifically targeting the epidermal growth factor receptor (EGFR) pathway are currently available for lung cancer treatment, none of them can escape their eventual drug-resistance. As a key component of Cordyceps Sinensis and widely used in traditional Chinese medicines (TCM), cordycepin (CD) has attracted increasing attention to both scientists and clinicians. We aimed to explore the potential in developing cordycepin (CD) as an anti-lung cancer drug. A systematic analysis was conducted on a panel of non-small cell lung cancer (NSCLC) cell lines to identify the cells sensitive to CD. We found that CD can affect different aspects of lung cancer development including proliferation, migration, invasion, cell cycle, and apoptosis. We then explored the underlying molecular mechanisms of CD-mediated NSCLC cell apoptosis by conducting a series of in vitro and in vivo experiments. We found that in addition to affecting different stages of NSCLC development including tumor growth, migration, and invasion, the CD is capable of inhibiting NSCLC cell cycle progression and inducing cancer cell apoptosis without apparent adverse effect on normal lung cells. Furthermore, we found that the cells containing EGFR mutations are more sensitive to CD treatment than those without. Mechanistically, CD induces NSCLC cell apoptosis by interacting with and activating AMP-activated protein kinase (AMPK). More importantly, we found that the potency of CD's anticancer effect both in vitro and in vivo is comparable to afatinib and even better than gefitinib. Our findings suggest that CD either by itself or in combination with the currently available targeted therapeutic drugs might be additional therapeutic options for drug-resistance NSCLC treatment.